EVALUASI KERUSAKAN BARANG DALAM PROSES PENGIRIMAN DENGAN MENGGUNAKAN METODE SIX SIGMA - Alif Fikri Dzulfikar; Ariyano Ariyano; Saskia Kanisaa Puspanikan (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2025)
Product damage during the delivery process can reduce customer satisfaction and negatively impact the image and performance of logistics service companies. This study aims to evaluate the level of product damage during the delivery process at PT X and to analyze the quality of the process using the Six Sigma approach. A quantitative method was employed using the DMAIC model (Define, Measure, Analyze, Improve, Control). Data were collected through observation, documentation, and interviews, and analyzed using the Seven Tools. The data processing results indicate that the damage rate between February and May 2024 reached 0.38%, with a DPMO value of 1,278 and a sigma level of 4.38. The dominant cause of damage was identified as human-related factors, such as carelessness during loading and unloading, and rushed driving. Recommended improvements include enhancing employee training, optimizing standard operating procedures (SOPs), increasing the number of delivery vehicles, and improving packaging material quality. This study concludes that the Six Sigma method is effective in evaluating and improving delivery quality and can serve as a reference for strategic decision-making aimed at reducing damage rates..